Employing artificial intelligence applications in conducting research: Effectiveness and challenges from the perspective of faculty members and graduate students in Emirati Universities - Alderbashi, Khaled Younis (International Journal of Innovative Research and Scientific Studies, 2025)
The current study aimed to identify the effectiveness of employing artificial intelligence (AI) applications in conducting research from the perspective of faculty members and graduate students in Emirati universities. It also aimed to identify the challenges hindering such use. The researcher adopted quantitative, qualitative, and descriptive analytical approaches. He designed a five-point Likert questionnaire to collect data about such effectiveness. He uploaded it to Google Forms. He distributed it to several WhatsApp groups to collect data from faculty members and graduate students in five Emirati private universities. Sixty-five faculty members and one hundred sixty graduate students (including males and females) filled in the questionnaire forms. In addition, the researcher interviewed fifteen faculty members and twenty graduate students (including males and females) who were chosen from the same universities to identify such challenges. Thus, the researcher used the purposive sampling technique in this study. It was found that using AI applications in conducting research is effective. The challenges hindering such use include facing technical problems while using these applications. The researcher recommends offering faculty members free access to some AI applications that can assist them in the research process.